Some tips on age estimation using DNA methylation in saliva samples as an index across the Japanese and Indonesian ethnicities. (May 2022) - Oka, Hiroko; Dwi Ariani, Maretaningtias; Akazaki, Tomohiko; Miyauchi, Mutsumi; Kitagawa, Masae
Highlights: Significant differences were observed in some methylation scores between different nationalities. Including race information may increase DNA methylation age estimation accuracy in some cases. MS-HRM can be a convenient method for age estimation via RT-PCR. Abstract: Age estimation of unidentified bodies is of marked importance in forensic medicine. In previous studies, the analysis of DNA methylation in body fluids led to the identification of several age-related CpG sites in genes such as EDARADD and FHL2 . However, limited information is available on whether interethnic differences may affect the age prediction results. In the present study, we examined the effect of ethnicity on the age prediction method based on methylation scores, which were determined via methylation-sensitive high-resolution melting. We found that there was a significant difference in methylation scores between Japanese and Indonesian participants of early 20 s group, and that the nationality coefficient was significant for age estimation when applying the existing method for the analysis of the methylation status of EDARADD and FHL2 . This suggests that when using certain biochemical indicators as a predictor of age, the effects of ethnicity on DNA methylation should be considered to improve the accuracy of the estimation.